Underutilized fruit crops in Egypt - Mansour K.M. (Underutilized fruit crops in the Mediterranean region, 1995)
Among the five underutilized fruits (fig, pomegranate, Barbary fig, persimmon and loquat), the first three are common in Egypt. Persimmon and loquat are less common and are known to few people. However, there are indications that their acreage and production are constantly increasing. Almost all the varieties of these fruits are local ones with local names, except in the case of kaki and loquat.
First meeting of the CIHEAM Cooperative Working Group on Underutilized Fruit Crops in the Mediterranean Region, 1994/11/09-10, Zaragoza (Spain)